PERAN PENETAPAN HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI KOPI 66 SELOPANGGUNG KEDIRI - Nurhalimah, Fitria; Sumantri, Bambang Agus; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2024)
This research aims to analyze the influence of price, product quality, and service quality on purchasing decisionsat Kedai Kopi 66 Selopanggung Kediri. This research uses quantitative methods with explanatory research. Therespondents in this study were 40 people, and the sampling used a non-probability sampling method. The dataanalysis method in this research uses validity testing, reliability testing, and hypothesis testing. Based on theresearch results, several conclusions can be drawn: 1) Price partially has a significant effect on purchasingdecisions at Kedai Kopi 66 Selopanggung Kediri. 2) Product quality partially influences purchasing decisions atKedai Kopi 66 Selopanggung Kediri. 3) Service quality partially significantly affects purchasing decisions at KedaiKopi 66 Selopanggung Kediri. 4) Price, product quality, and service quality simultaneously significantly influencepurchasing decisions at Kedai Kopi 66 Selopanggung Kediri.